The Bronze Age Fortifications in Munar “Wolfsberg”, Arad County. The 2014 and 2017 Archaeological Researches - Sava, Victor; Gogâltan, Florin (Analecta Archaeologica Ressoviensia, 2017)
In spite that the Bronze Age site Munar “Wolfsberg” has been depicted on the Josephine topographic survey (late 18th century), the first scientific data focusing on this site occurs at the beginning of the 20th century. As “Wolfsberg” did not have the dimensions of the nearby prehistoric fortifications at Sântana and Corneşti, the site was not targeted by archaeological investigations and it has only been occasionally mentioned in the secondary literature so far. During the year 2014 a team of researchers have started the investigations with the site’s topographic survey, followed by a systematic ground survey, geophysical measurements, as well as aerial photographs. Three years later, a small test trench was excavated in order to attempt dating the Middle Bronze Age tell in terms of the absolute chronology.